Semantics Structure of Javanese Proverbs: A Natural Semantic Metalanguage Analysis - Puguh Dwi Siswoyo; Deli Nirmala (Program Studi Ilmu Perpustakaan, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
This study is aimed to investigate the explication of Javanese proverbs, and also to find the NSM semantic template pattern in Javanese language proverbs. This study integrates natural semantic metalanguage (NSM) into the semantic analysis to explain how the meaning of Javanese proverbs can be explained. In this study, the researcher uses a five-semantic template for English proverbs proposed by Goddard and Wierzbicka. The findings of the study indicate that not all of the semantic template is fulfilled in Javanese Proverbs. It means that there is not any pattern of NSM semantic template in Javanese language. However, the application of NSM sematic templates in explaining proverbs meaning is not only worthwhile but also practical in explicating the Javanese proverbs.